Reflection in the writing classroom - Yancey, Kathleen Blake, 1950- (Utah State University Press, 1998)
Yancey explores reflection as a promising body of practice and inquiry in the writing classroom. Yancey develops a line of research based on concepts of philosopher Donald Schon and others involving the role of deliberative reflection in classroom contexts. Developing the concepts of reflection-in-action, constructive reflection, and reflection-in-presentation, she offers a structure for discussing how reflection operates as students compose individual pieces of writing, as they progress through successive writings, and as they deliberately review a compiled body of their work-a portfolio, for example. -- Provided by publisher.